SHARING OF FINDINGS AND RECOMMENDATIONS REMAINS A FALLACY”: REINVIGORATION OF THE DISSEMINATION AND IMPLEMENTATION OF SOCIAL WORK DOCTORAL RESEARCH FINDINGS - Makofane, Mankwane (Social Work/Maatskaplike Werk, 2018)
Research is the backbone of social work knowledge and practice. A qualitative study conducted to explore and describe the dissemination of research findings and implementation of practice recommendations among 31 doctoral graduates revealed that these processes seemed to be a mere afterthought. Sixteen graduates published articles from their theses, ten conducted workshops, another ten applied practice recommendations, while four published the findings and applied their recommendations. An indaba is suggested to develop a framework for the dissemination and use of recommendations through networks.